Essential knowledge of the professional profile for a master's degree in teacher training in technical education in Costa Rica - Quirós Durán, Scarlett (2024)
The growing interest in expanding and improving Technical Vocational Education and Training (TVET) in Costa Rica is becoming increasingly evident. Therefore, different institutions, including the Institute for Research in Education (INIE) of the University of Costa Rica, have promoted research in this area. The present exploration aims to identify, among other aspects, the essential knowledge that future professionals who pursue a master's degree in technical education with an emphasis on pedagogical mediation must possess. This degree arises as a need in the educational context in which teachers who teach classes in different TVET institutions must reinforce their knowledge and skills around the teaching-learning process, focusing on competency-based education. This predominantly qualitative mixed research took place between 2020 and 2022. It is oriented towards the analysis of the TVET requirements that teachers have, to determine the essential knowledge that characterizes the professional academic profile in this field. A documentary review, interviews, questionnaires and focus groups were used with key TVET actors (teachers from the Ministry of Public Education and the National Learning Institute, employers in these sectors, directors or people in charge of TVET study programs, specifically, from the Technological Institute of Costa Rica (TEC) and the National Technical University (UTN), and experts in the field of TVET). Six interviews and 326 questionnaires were applied, in addition to several focus group sessions. According to the results obtained, it is determined that the main knowledge and skills must focus on the technical specialty they teach, on the implementation of information and communication technologies that enrich the educational process, on taking into account the work environment in which students may be inserted later to prepare them in the best way, considering, among other aspects, the development of soft skills, as well as the adequate implementation of a competency-based approach. Furthermore, with respect to knowing how to be and live together, a series of attitudes and values are established that teachers in charge of TVET must develop and show. It is concluded that the TVET teacher requires a complex professional profile that includes different knowledge that must be constantly reflected and updated.